Teachers and students' perceptions of the adequacy of upper basic social studies curriculum as a tool for citizenship participation and national security (2016)
The security challenges faced by Nigeria have resulted in incessant closure of schools which has had adverse effects on the educational sector. This study investigated teachers and students' perception of the adequacy of Upper Basic Social Studies Curriculum as a tool for citizenship participation and national security. The study is a survey research type that adopted multi-stage sampling technique. 300 students and 35 teachers from fifteen Junior Secondary Schools were selected for this study. Six research questions were answered and two validated instruments were used. Data were analysed using descriptive statistics and t-test. Results indicated that students have a significantly better perception with t-value = 5.81, p< 0.05 on the adequacy of the curriculum as a tool for citizenship participation while teachers have a significantly greater perception with t-value = 3.28, p < 0.05 as a tool for national security. Policy makers and curriculum planners should ensure that teachers make adequate use of the curriculum by doing proper monitoring.